Financial integration and efficiency of the financial sector in the ECCB area. - AUGUSTINE, C. (1995)
Attempts to measure the extent of financial integration by comparing inter-bank and non-resident transactions within and outside the ECCB area. Identifies some major actions which would be necessary to enhance financial integration and the efficiency of financial markets in the area.